Barium isotope fractionation during witherite (BaCO3) dissolution, precipitation and at equilibrium. (1st October 2016) - Mavromatis, Vasileios; van Zuilen, Kirsten; Purgstaller, Bettina; Baldermann, Andre; Nägler, Thomas F.; Dietzel, Martin
Abstract: This study examines the behavior of Ba isotope fractionation between witherite and fluid during mineral dissolution, precipitation and at chemical equilibrium. Experiments were performed in batch reactors at 25 °C in 10 −2  M NaCl solution where the pH was adjusted by continuous bubbling of a water saturated gas phase of CO2 or atmospheric air. During witherite dissolution no Ba isotope fractionation was observed between solid and fluid. In contrast, during witherite precipitation, caused by a pH increase, a preferential uptake of the lighter 134 Ba isotopomer in the solid phase was observed. In this case, the isotope fractionation factor αwitherite-fluid is calculated to be 0.99993 ± 0.00004 (or Δ 137/134 Bawitherite-fluid  ≈ −0.07 ± 0.04‰, 2 sd). The most interesting feature of this study, however, is that after the attainment of chemical equilibrium, the Ba isotope composition of the aqueous phase is progressively becoming lighter, indicating a continuous exchange of Ba 2+ ions between witherite and fluid. Mass balance calculations indicate that the detachment of Ba from the solid is not only restricted to the outer surface layer of the solid, but affects several (∼7 unit cells) subsurface layers of the crystal. This observation comes in excellent agreement with the concept of a dynamic system at chemical equilibrium in a mineral–fluid system, denoting that the time required for the achievement of isotopic equilibrium in the witherite–fluid system is longer compared to that observed for chemical equilibrium. Overall, these results indicate that the isotopic composition of Ba bearing carbonates in natural environments may be altered due to changes in fluid composition without a net dissolution/precipitation to be observed.